Biodegradable, Super-Strong, and Conductive Cellulose Macrofibers for Fabric-Based Triboelectric Nanogenerator - Hu, Sanming; Han, Jing; Shi, Zhijun; Chen, Kun; Xu, Nuo; Wang, Yifei; Zheng, Ruizhu; Tao, Yongzhen; Sun, Qijun; Wang, Zhong Li; Yang, Guang (Nano-Micro Letters, 2022)
Electronic fibers used to fabricate wearable triboelectric nanogenerator (TENG) for harvesting human mechanical energy have been extensively explored. However, little attention is paid to their mutual advantages of environmental friendliness, mechanical properties, and stability. Here, we report a super-strong, biodegradable, and washable cellulose-based conductive macrofibers, which is prepared by wet-stretching and wet-twisting bacterial cellulose hydrogel incorporated with carbon nanotubes and polypyrrole. The cellulose-based conductive macrofibers possess high tensile strength of 449 MPa (able to lift 2 kg weights), good electrical conductivity (~ 5.32 S cm−1), and excellent stability (Tensile strength and conductivity only decrease by 6.7% and 8.1% after immersing in water for 1 day). The degradation experiment demonstrates macrofibers can be degraded within 108 h in the cellulase solution. The designed fabric-based TENG from the cellulose-base conductive macrofibers shows a maximum open-circuit voltage of 170 V, short-circuit current of 0.8 µA, and output power at 352 μW, which is capable of powering the commercial electronics by charging the capacitors. More importantly, the fabric-based TENGs can be attached to the human body and work as self-powered sensors to effectively monitor human motions. This study suggests the potential of biodegradable, super-strong, and washable conductive cellulose-based fiber for designing eco-friendly fabric-based TENG for energy harvesting and biomechanical monitoring. Highlights: 1 The cellulosed-based macrofibers possess super-strong tensile strength of 449 MPa and excellent electrical conductivity of 5.32 S cm−1. 2 The cellulosed-based macrofiber can be degraded within 108 h in the cellulase solution. 3 The designed fabric-based triboelectric nanogenerator (TENG) shows a maximum output power of 352 μW, which can effectively drive commercial electronics. 4 The designed fabric-based TENG as self-powered sensors can effectively monitor the human movement of walking, running, jumping, arm lifting, arm bending, and leg lifting.